Mindful Parenting dan Parental Mediation dalam Perspektif Islam dan Psikologi - Nurzuhriyah A. Kasuba; Zulfa Febriani; Karimulloh Karimulloh (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Industrial era 4.0 provides accessibility to smartphone use on early childhood. The negative or positive impact depending on how parents introduce smartphones to children through parental mediation strategies. Parents’ character plays a role in shaping children’s behavior and discipline, especially parents with mindful parenting. This study aims to examine the relationship between mindful parenting and parental mediation from the psychological and Islamic perspective. We used a mixed method with sequential explanatory design. Mindfulness in Parenting Questionnaire (MIPQ) and Parental Mediation Questionnaire (PMQ) was used as measuring instrument with a total of 131 parents who have children aged 3-6 years participated in this study. The results show that mindful parenting correlates significantly to the active mediation strategy while its relationship was weak with restrictive mediation. In the Islamic perspective, when parents rely on all responsibilities and rights that must be given to children with the intention of worshiping Allah, parents will apply the rules to their children according to Islamic law.Industrial era 4.0 provides accessibility to smartphone use on early childhood. The negative or positive impact depending on how parents introduce smartphones to children through parental mediation strategies. Parents’ character plays a role in shaping children’s behavior and discipline, especially parents with mindful parenting. This study aims to examine the relationship between mindful parenting and parental mediation from the psychological and Islamic perspective. We used a mixed method with sequential explanatory design. Mindfulness in Parenting Questionnaire (MIPQ) and Parental Mediation Questionnaire (PMQ) was used as measuring instrument with a total of 131 parents who have children aged 3-6 years participated in this study. The results show that mindful parenting correlates significantly to the active mediation strategy while its relationship was weak with restrictive mediation. In the Islamic perspective, when parents rely on all responsibilities and rights that must be given to children with the intention of worshiping Allah, parents will apply the rules to their children according to Islamic law.